2018
DOI: 10.15405/epsbs.2018.11.02.39
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad Of Personality In Kindergarten, School And University Teachers

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The regression analysis has shown that the Dark Triad significantly predicts the development of emotional exhaustion at a rate of 15.7% and depersonalization at a rate of 23.5%, psychopathy was the most important predictor in both cases. This result is not surprising when looking at the research of Lenkov et al (2018), which points to a significant level of psychopathy among secondary school teachers compared to elementary and secondary school teachers. More comprehensive testing of Dark Triad-burnout syndrome relationship suggests that up to 58% of burnout syndrome can be explained by the presence of aversive personality traits.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The regression analysis has shown that the Dark Triad significantly predicts the development of emotional exhaustion at a rate of 15.7% and depersonalization at a rate of 23.5%, psychopathy was the most important predictor in both cases. This result is not surprising when looking at the research of Lenkov et al (2018), which points to a significant level of psychopathy among secondary school teachers compared to elementary and secondary school teachers. More comprehensive testing of Dark Triad-burnout syndrome relationship suggests that up to 58% of burnout syndrome can be explained by the presence of aversive personality traits.…”
Section: Discussionmentioning
confidence: 89%
“…As suggested above, much of the teacher´s personality research is focused on identifying teacher´s positive personality traits, with the Big Five perspective most often used (Berkovich and Eyal, 2019;Kalinnikova et al, 2018;Rohani, 2017;Tamban and Banasihan, 2017;Tan, Marsi and Furnham, 2018). As Lenkov, Rubtsova and Nizamova (2018) state, much less attention has been paid to the other side of the teacher's personality. A more comprehensive view of his personality, thus from both the bright and the dark perspective, could explain the diversity of teacher responses in the performance of their vocation.…”
Section: The Dark Triad and Teaching Professionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies where students from different directions would be compared in this way are not known. However, there are studies that point to a higher rate of aversive traits in healthcare professionals (Admas & Maykut, 2015;Bakir et al, 2003;Bratek et al, 2015;Bucknall et al, 2015;Pegrum & Pearce, 2015), pedagogical workers (Lenkov et al, 2018) and social workers (Babiak, 1995;Selingson, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In their work, Adams and Maykut (2015) discussed the potential dangers of inappropriate care of nurses and other medical staff if they would have dark features. Lenkov, Rubtsova and Nizamova (2018) recorded the highest incidence of dark personality traits among university teachers. More detailed results showed a significantly higher level of psychopathy among elementary and secondary school teachers.…”
Section: Dark Triad and Helping Professionsmentioning
confidence: 96%